THE STUDY OF REGULARITIES OF THE DIFFUSION OF CARBON IN THE SURFACE LAYER OF STEEL 12KH18N10T - I. R. Kuzeyev; S. V. Popova; A. N. Vasiliev (Литьë и металлургия, 2012)
Researches of carbonized layer of steel 12х18Н10Т are carried out. The new effect at distribution of the carbon front in the course of chemical and thermal processing of this steel is revealed